2016
DOI: 10.1002/cbdv.201500215
|View full text |Cite
|
Sign up to set email alerts
|

Sterols and Fatty Acids of the Harmful Dinoflagellate Cochlodinium polykrikoides

Abstract: Sterol and fatty acid compositions were determined for Cochlodinium polykrikoides, a toxic, bloom-forming dinoflagellate of global significance. The major sterols were dinosterol (40% of total sterols), dihydrodinosterol (32%), and the rare 4α-methyl Δ(8(14)) sterol, amphisterol (23%). A minor sterol, 4α-methylergost-24(28)-enol was also detected (5.0%). The fatty acids had a high proportion of PUFAs (47%), consisting mainly of EPA (20%) and the relatively uncommon octadecapentaenoic acid (18 : 5, 22%). While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Collected data were analyzed with an Agilent GC/MSD Productivity ChemStation and AMDIS (Automated Mass spectral Deconvolution and Identification System) software. Sterols were identified by comparing their retention times and mass spectra to those of sterols from dinoflagellates and other marine organisms (65)(66)(67)(68)(69)(70)(71)(72)(73)(74) and to entries in the commercial NIST/EPA/NIH Mass Spectral Library (NIST 08) GC/MS database. Sterols with similar mass spectra were identified by comparing their relative retention times with respect to cholesterol and retention indices to published values or values in the NIST database.…”
Section: Methodsmentioning
confidence: 99%
“…Collected data were analyzed with an Agilent GC/MSD Productivity ChemStation and AMDIS (Automated Mass spectral Deconvolution and Identification System) software. Sterols were identified by comparing their retention times and mass spectra to those of sterols from dinoflagellates and other marine organisms (65)(66)(67)(68)(69)(70)(71)(72)(73)(74) and to entries in the commercial NIST/EPA/NIH Mass Spectral Library (NIST 08) GC/MS database. Sterols with similar mass spectra were identified by comparing their relative retention times with respect to cholesterol and retention indices to published values or values in the NIST database.…”
Section: Methodsmentioning
confidence: 99%
“…Mucopolysaccharides produced by M. polykrikoides may be attributed to the smothering of fishes (Kim and Oda, 2010), but no study has affirmed this finding and there were no visual signs of polysaccharides on fish during our study. Giner et al (2016) extracted lipids of M. polykrikoides cells and analyzed the compositions of fatty acid and sterol in crude lipids, which consisted of a high proportion of PUFAs (47% of total fatty acids), dinosterol (40% of total sterols), and dihydrodinosterol (32% of total sterols). The identified fatty acids and sterols may contribute to long-term deleterious effects on invertebrates but were unlikely to be effective substances responsible for the acute toxicity to fish (Giner et al, 2016).…”
Section: Expectations In Identifying Toxins and Allelochemicals Of M ...mentioning
confidence: 99%
“…The toxins of M. polykrikoides cause damage to different cell types, including hemolysis in fish erythrocytes (Kim et al, 1999;Dorantes-Aranda et al, 2009a;Kim and Oda, 2010). The conceivable ichthyotoxic substances produced by M. polykrikoides have been hypothesized to include reactive oxygen species (ROS) (Tang and Gobler, 2009a), sterols, fatty acids (Giner et al, 2016), and mucopolysaccharides (Kim et al, 2002;Kim and Oda, 2010). The short-term nature of M. polykrikoides toxicity (minutes in the absence of live cells) and the ability of anti-oxidation compounds to mitigate its toxicity have suggested that ROS are a likely source of this HABs toxicity (Tang and Gobler, 2009b;Jiang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the diversity of numerous microalgal free sterols was found to be higher in comparison with that of higher plants. Sterol compositions of microalgae were discussed in numerous works, which considered the chemotaxonomic importance of these compounds, their application as markers for marine and terrigenous organic matter, their significance for marine life, and their influence on the development of their producers in wild conditions and cultures [9,10,11,12,13,20,26,27].…”
Section: Sterols and Sterol Glycoconjugates Structural Diversity mentioning
confidence: 99%